Servicio militar y la construcción nacional: notas sobre el origen de la institución - Toche, Eduardo (2005)
The Armed Forces were an important component of the modern states that arose in Latin America at the end of the 19th century. At the same time, the Obligatory essential part of the prevailing European models, the Obligatory Service contained cultural and social permises that were those of our countries. In this manner, a lot of imagination should have been employed to implement it without distorting the objectives of the referred models. So, a mechanism conceived to organize the citizens in the defense of the country, besides being sean as limited in this functions, should have fulfilled other tasks that formed part of the project.